Studi Pemanfaatan Limbah Eksploitasi Hutan Di Kalimantan Barat Untuk Industri Papan Partikel - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1995)
ABSTRACT A study on forest exploitation wood waste used as a raw material for particle board industry is reported The result showed that production cost of wood waste from forest exploitation (Rp 32,500Im3) was higher than from wood waste (Rp 15,000Im3). Production cost of particle board using forest exploitation wood waste (Rp 262,512.92Im3), was higher than the price of particle board (Rp 257,610.30Im3).